Apparent lack of spill-over of parasites from an invasive anuran: PCR detects Entamoeba in cane toads (Rhinella marina) but not in sympatric Australian native frogs - Rivory, Phoebe (Int J Parasitol Parasites Wildl, 2020)
The recent detection of a novel amoebozoan parasite (Entamoeba sp. CT1) killing invasive cane toads (Rhinella marina) in tropical Australia raises concerns of potential spill-over into native anuran populations. Considering the vulnerability of anuran communities globally, Entamoeba sp. CT1 may pose a serious threat to anuran biodiversity. Through PCR-based detection and molecular identification, we investigated the prevalence of Entamoeba spp. in the faeces and colon tissue of cane toads (Rhinella marina) and eleven native Australian frog species from a single locality in the Northern Territory. No Entamoeba DNA was detected in samples of native frog faeces (N = 57) or colons (N = 17). Entamoeba DNA was detected in 24% of 45 cane toads (95%CI 14.08–38.82). Both E. ranarum and Entamoeba sp. CT1 were present in cane toads. The failure of faecal samples to indicate Entamoeba spp. in infected cane toads may be due to cysts in faeces being shed intermittently, degraded before analysis, or impervious to lysis prior to DNA isolation. Our results suggest that native frogs do not carry the pathogen in an area where 20–30% of cane toads are infected with Entamoeba sp. CT1. We demonstrate the importance of recognising PCR inhibition prior to molecular diagnostics, and the apparent inadequacy of faecal samples for the detection of Entamoeba spp. in anurans.